PENGENALAN KEWIRAUSAHAAN PEMBUATAN HANDSANITISER PADA SISWA DAN SISWI SMK MUHAMMADIYAH 1 KOTA BEKASI DENGAN PENERAPAN MODEL AL (ACTIVE LEARNING) - Micky Prathama; Daru Susanti; Djihadul Mubarok (Institut Bisnis Muhammadiyah Bekasi, 2022)
Secondary-level education, especially SMK has a unique character in producing graduates who are ready to work. The real potential of SMK graduates is not only ready to work, but has a great opportunity to participate in developing the economy through entrepreneurship. On this basis, research on the development of entrepreneurship was then carried out on students of SMK Muhammadiyah 1 Bekasi using the AL (Active Learning) method. The basic principle of the AL method is the involvement of students in the active learning process of participants in entrepreneurship. The type of business conveyed was the manufacture of Baitullah- scented Hand sanitiser products with learning materials from the introduction of raw materials to the calculation of the Cost of Goods. Meanwhile, the AL learning stage itself starts from the delivery of material to the opportunity for students and students to make presentations. The results of the response of students and students to the implementation of Active Learning from the questionnaire obtained by 86% of students expressed satisfaction with this learning. However, there are still some students who are not satisfied to be able to review the improvements in the application of learning.